Kompetensi Komunikasi Penyiar pada Radio Komunitas Islami dalam Transisi Digital: Studi Kasus Radio Purbowangi FM, Indonesia - Febriany, Febriany; Sahran Putri, Pusparani; Iqbal Maulana, Mohammad; Rofi Ardliansyah, Muhammad; Akmaludin, Nur (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2025)
Islamic community radio is increasingly challenged by media convergence and changing audience habits during digital transition. This study examines how broadcasters’ communication competence functions as a key mechanism for sustaining audience engagement and loyalty in Radio Purbowangi FM, Indonesia. Using a qualitative case study design, data were collected through in-depth interviews with five informants (two broadcasters, one technician, and two listeners), participant observation of on-air and off-air activities, and document analysis of programme recordings and audience interactions. The data were analyzed thematically using Spitzberg and Cupach’s communication competence framework, comprising knowledge, motivation, and skills. The findings indicate that: (1) knowledge is reflected in broadcasters’ understanding of moderate Islamic values, sensitivity to local culture, and their ability to tailor messages to audience segments; (2) motivation is evidenced by a service-oriented and prosocial commitment, including broadcasters’ roles as community information brokers and active participation in local activities; and (3) skills are demonstrated through dialogic on-air delivery, real-time responsiveness via interactive channels (e.g., phone/WhatsApp), technical mastery of broadcasting, and adaptation to selected digital channels such as live streaming, alongside promotional collaboration with local MSMEs. Overall, the study highlights communication competence as a stabilizing resource that enables Islamic community radio to remain relevant and socially embedded amid digital transition.